Recent Advances in Second Near-Infrared Region (NIR-II) Fluorophores and Biomedical Applications - Chen, Yingying; Xue, Liru; Zhu, Qingqing; Feng, Yanzhi; Wu, Mingfu (Frontiers in Chemistry, 2021)
Fluorescence imaging technique, characterized by high sensitivity, non-invasiveness and no radiation hazard, has been widely applicated in the biomedical field. However, the depth of tissue penetration is limited in the traditional (400–700 nm) and NIR-I (the first near-infrared region, 700–900 nm) imaging, which urges researchers to explore novel bioimaging modalities with high imaging performance. Prominent progress in the second near-infrared region (NIR-II, 1000–1700 nm) has greatly promoted the development of biomedical imaging. The NIR-II fluorescence imaging significantly overcomes the strong tissue absorption, auto-fluorescence as well as photon scattering, and has deep tissue penetration, micron-level spatial resolution, and high signal-to-background ratio. NIR-II bioimaging has been regarded as the most promising in vivo fluorescence imaging technology. High brightness and biocompatible fluorescent probes are crucial important for NIR-II in vivo imaging. Herein, we focus on the recently developed NIR-II fluorescent cores and their applications in the field of biomedicine, especially in tumor delineation and image-guided surgery, vascular imaging, NIR-II-based photothermal therapy and photodynamic therapy, drug delivery. Besides, the challenges and potential future developments of NIR-II fluorescence imaging are further discussed. It is expected that our review will lay a foundation for clinical translation of NIR-II biological imaging, and inspire new ideas and more researches in this field.